2016
DOI: 10.1002/jctb.4902
|View full text |Cite
|
Sign up to set email alerts
|

Metal distribution in the process of lignocellulosic ethanol production from heavy metal contaminated sorghum biomass

Abstract: BACKGROUND: The objective of this work was to process the sorghum biomass obtained from crops cultivated on heavy metals polluted soil, for the production of lignocellulosic ethanol and to determine the amount of toxic metals in the intermediary, byproducts, and final products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Various studies have been conducted to determine reducing sugar (glucose) and ethanol yield from lignocellulosic biomass [30,57,58,59]. Typically, most of the lignocellulosic biomass from agriculture consists of about 40%-50% cellulose, 20%-30% hemicellulose, and 10%-25% lignin [60].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted to determine reducing sugar (glucose) and ethanol yield from lignocellulosic biomass [30,57,58,59]. Typically, most of the lignocellulosic biomass from agriculture consists of about 40%-50% cellulose, 20%-30% hemicellulose, and 10%-25% lignin [60].…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that the first three best potentials in terms of sugar production per hectare are hybrids F135ST, Sugargraze II and Sugargraze, in the range of 4500 -7000kg/ha. These sugars obtained in polluted area can be used in biorefinery to produce biofuels and other biochemical, as described in our previous research [13], and bagasse can be used as co-substrate in anaerobic digestion for biogas production. In the same previous work, data indicate that the metal concentrations in sorghum juice obtained in the same polluted area are below the established maximal thresholds; therefore, the sorghum juice can be used in food industry as well.…”
Section: B Sugar Extractionmentioning
confidence: 98%
“…Sorghum cultures have been previously applied in phytoextraction experiments in in polluted areas [10]- [12]. Our research results indicated sweet sorghum as a good alternative to use heavy metals polluted land for fuel bioethanol production [13]. In this regard, the aim of this study was to evaluate the potential of sugars production of several sweet sorghum hybrids cultivated in heavy metals polluted area.…”
Section: Introductionmentioning
confidence: 98%
“…The Patent Application is registered to Romanian Office for Inventions and Marks. "This invention brings an extremely important novelty, namely: treating lignocellulosic biomass by original patented process has better effect in terms of improving access of enzymes for hydrolysis of cellulose than conventional methods of thermalchemical pretreatment (alkaline/steam) " [20]. The treatment of biomass according to patenting process has triple effect: (1) preservation of sugars, (2) extraction of sugars and (3) release of cellulose from lignocellulosic complex and access of cellulolytic enzymes to hydrolyse cellulose to glucose.…”
Section: Bioeconomy and Rural Pole Development And Circular Economymentioning
confidence: 99%